Analysis of the Determinants of Academic Procrastination among Students an Intrinsic and Extrinsic Factors Perspective in the Context of Islamic Religious Education - Novia Firdayanti; Muhammad Wildan Shohib; Muh. Nur Rochim Maksum (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Universitas Muhammadiyah Surakarta Academic procrastination is a recurring issue among university students, including those enrolled in Islamic Religious Education (PAI) programs, and it negatively affects learning effectiveness and academic performance. This behavior is characterized by delaying the initiation, process, or completion of academic tasks despite being aware of the potential consequences. This study aims to identify and analyze intrinsic and extrinsic factors contributing to academic procrastination among PAI students based on findings from national empirical studies. This research employs a library research method by reviewing six national articles that meet the following criteria: (a) discussing determinants of academic procrastination, (b) focusing on PAI students or students in Islamic higher education institutions The findings reveal that dominant intrinsic factors include low learning motivation, weak self-regulation, physical and psychological fatigue, lack of self-confidence, and difficulty maintaining concentration. Meanwhile, dominant extrinsic factors consist of task overload, academic pressure, organizational commitments, digital distractions, online gaming addiction, weak lecturer student communication, and insufficient learning facilities. Additionally, some studies highlight that PAI students face additional challenges such as overlapping religious activity schedules and spiritual obligations, which may influence academic prioritization. These results demonstrate that academic procrastination among PAI students is a multidimensional phenomenon shaped by psychological, academic, environmental, and spiritual factors. Therefore, comprehensive intervention efforts are needed, including strengthening self-regulation, time management, and integrating Islamic spiritual values as an ethical foundation for academic discipline in Islamic higher education.